Thermodynamic Properties of Novel Branched Gemini Imidazolium Surfactants in Aqueous Solutions Based on Free Energy Perturbation. Issue 4 (8th March 2013) - Liu, Haiyan; Gu, Daming; Liu, Guoyu; Ding, Wei
Abstract: The thermodynamics properties of novel branched gemini imidazolium surfactants (BGIS) with different numbers of carbon atoms in the hydrophobic group or hydroxyl numbers of the spacer are studied by the free energy perturbation (FEP) model. In the FEP model, the Gibbs free energy contributions to the driving force for micelle formation are computed using hydration data obtained from molecular dynamics simulations. The thermodynamic properties of micellization in aqueous solutions for BGIS were discussed according to the pseudo‐phase separation model. The results show that the micellization of BGIS in aqueous solutions is a spontaneous and entropy‐driven process. It is linearly enthalpy‐entropy compensated. The compensation temperature of BGIS was lower for BGIS with hydroxyl group than without it at 297 ± 3 versus 307 ± 3 K. The contribution of entropy change to the micellization tends to decrease, while the contribution of enthalpy change tends to increase. In particular, as the number of hydroxyl groups in spacer is increased, the thermodynamic favorability and stability of the micelles of BGIS with hydroxyl group improve significantly.